Etiology and patterns of pediatric maxillofacial fractures in the Uzbekistan - Musaev Shamshodbek Shuxratovich; Shomurodov Kahramon Erkinovich; Narzieva Mahliyo Isrofil kizi (Elsevier, 2021)
In this study was to analyze the patterns of maxillofacial fractures in children under 18 years of age admitted at paediatric maxillofacial surgery department in Tashkent state dental institute, Uzbekistan in a period of 12 years between January 2007 and December 2018. Out of 757 children with maxillofacial bone fractures, the majority were aged between 6 and 18 years (78,6%, n = 595). The mean (±SD) age was 9.3 ± 0.5 years and male to female ratio was 6.2:1. Falls was the most frequent mode of injury (46,9%, n = 355). The mandible was most commonly involved (67.2%, n = 509) of the cases. The incidence of paediatrics maxillofacial fractures in Uzbekistan region was high. The 6-18-year olds and boys were most commonly involved in maxillofacial paediatrics trauma. Mandibular fractures were the most common type of fracture. Safety programs should be instituted in Uzbekistan region to increase public awareness and to decrease morbidity resulting from paediatrics maxillofacial trauma.